Faktor-Faktor Yang Berpengaruh Dalam Keputusan Pembelian Rumah Untuk Masyarakat Berpenghasilan Rendah - Andhika Mendrofa; Heri Wibowo; Ivan Sofyan; Taufiq Hendrawan; Wita Witria (Indonesian Business Review, 2018)
Focus of this research is to study factors influencing the decision-making to purchase houses for low-income communities (“MBR”) in which the objective is to find the factors considered by the MBR to purchase a house. The survey covers Jakarta, Bogor, Depok, Tangerang and Bekasi (“Jabodetabek”) conducted through online media and direct meeting with 251 respondents (188 respondents is categorized as the MBR and intend to purchase houses). Questionnaire uses Likert Scale with factor and descriptive analysis. Based on result, the considering factors are price, location, promotion, facilities and financing in which the most dominant factors are price and location.